2022
DOI: 10.1126/sciadv.abk3141
|View full text |Cite
|
Sign up to set email alerts
|

Targeted DamID in C. elegans reveals a direct role for LIN-22 and NHR-25 in antagonizing the epidermal stem cell fate

Abstract: Transcription factors are key players in gene networks controlling cell fate specification during development. In multicellular organisms, they display complex patterns of expression and binding to their targets, hence, tissue specificity is required in the characterization of transcription factor–target interactions. We introduce here targeted DamID (TaDa) as a method for tissue-specific transcription factor target identification in intact Caenorhabditis elegans animals. We use TaDa to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 61 publications
0
8
0
Order By: Relevance
“…Currently, ChIP-seq is the most commonly used method to identify binding targets (Kudron et al, 2018;Celniker et al, 2009). Recent studies presented here indicated that TaDa is comparable with ChIP-seq in identifying target genes (Katsanos & Barkoulas, 2022). In addition, TaDa offers the following two key advantages.…”
Section: Discussionmentioning
confidence: 87%
“…Currently, ChIP-seq is the most commonly used method to identify binding targets (Kudron et al, 2018;Celniker et al, 2009). Recent studies presented here indicated that TaDa is comparable with ChIP-seq in identifying target genes (Katsanos & Barkoulas, 2022). In addition, TaDa offers the following two key advantages.…”
Section: Discussionmentioning
confidence: 87%
“…With the recent report of the wild-type AC transcriptome (Costa et al, 2023) and advancements in single-cell chromatin and transcription factor profiling (Fabian et al, 2022; Katsanos and Barkoulas, 2022; Katsanos et al, 2021; Yee et al, 2023), the application of these genomic profiling technologies should enable a mechanistic understanding of how the invasive differentiation program can be uncoupled from cell cycle exit. We hope that our results will provide a framework for a better understanding of the interplay between cell cycle exit, terminal differentiation, and cell invasion during normal development and disease states such as cancer metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Direct targets of NHR-67 have not yet been discovered, which makes it difficult to investigate this specific aspect of the repressive mechanism at present. We see this as a promising avenue of future study as technologies advance, allowing for transcriptional profiling and target identification in specific tissues or cells (Gómez-Saldivar et al, 2020;Katsanos and Barkoulas, 2022).…”
Section: Discussionmentioning
confidence: 99%